Using Card Games to study cultural differences in men's social talk about prostate cancer. (25th April 2020) - Fry, Sarah L.; Kelly, Daniel; Hopkinson, Jane
Abstract: Aim: To report the Card Games approach used to study men's talk about their risk for prostate cancer and as a method of data collection to analyse patterns of talk among distinct cultural groups. Design: A constructivist grounded theory approach using focus groups to analyse men's social talk about prostate cancer. Methods: Data were collected using three focus groups with African‐Caribbean, Somali, and White British men. The focus groups were conducted in a location of the men's choice with a focus group facilitator and observer. Four Card Games were given to the men to encourage social talk. Results: The African‐Caribbean men had the most democratic talk with the use of agreement and disagreement and the Somali men were the most inclusive of others and used the most humour. The White British men were competitive in their talk and the least inclusive of each other's views. Conclusion: The Card Games revealed differences in the pattern of talk, which provided insight into how men may use social talk to develop their understanding of prostate cancer risk. This is useful for healthcare professionals as it provides a grounding for structuring discussions with men about prostate cancer, while understanding of how risk‐related knowledge may be reconstructed in social talk and interactions. Impact: The methodology discussed in this paper addressed the use of focus group to analyse talk of men from culturally diverse groups. The use of Card Games allowed the talk between the men to take centre stage and this allowed differences in the social talk of the men to become apparent. The use of this methodology could have an impact on approaches to researching cultural understandings of cancer risk, which may provide evidence on effective delivery of sociocultural relevant health education relating to cancer screening. Abstract : 目的: 报告使用纸牌游戏研究男性前列腺癌风险的话题, 并作为一种数据收集方法, 分析不同文化群体之间的谈话模式。 设计: 以构成主义实地理论方法, 使用焦点小组分析男性前列腺癌的社会话题。 方法: 采用非洲加勒比黑人、索马里和英国白人男性三个焦点组收集数据。由一名焦点小组主持人和观察员在选定男性的地区进行焦点小组。为鼓励人们交谈, 给他们四种游戏的纸牌。 结果: 非洲裔加勒比男性以同意和不同意的方式开展谈论, 最为民主;索马里男性的谈话最包容和最幽默。英国白人男性的谈话中充满竞争意味, 对彼此的观点最不包容。 结论: 纸牌游戏揭示了谈话模式的差异, 为了解男性如何利用社交谈话来提高对前列腺癌风险的认识提供依据。这对医疗护理人员很有用, 其为与男性展开前列腺癌的讨论提供了依据, 同时了解如何在社交谈话和互动中重建风险相关知识。 影响: 本文讨论的方法是利用焦点小组分析来自不同文化群体的男性的谈话。使用纸牌游戏使得男人之间的谈话成为核心, 并明显显示出这些人群之间的社交谈话差异。这一方法的使用可能会影响对研究癌症风险的文化理解方法, 其可能为有效开展与癌症筛查社会文化相关的健康教育提供证据。